Causes of maternal mortality and the effectiveness of healthcare services: a retrospective analysis in Adana province - Sucu, Mete; Uzay, Fatma İşlek (Scientific Reports in Medicine, 2026)
Objective: This study aims to retrospectively analyze maternal deaths occurring in Adana province between 2011 and 2016, evaluating the causes of death, demographic and clinical characteristics, and access to healthcare services.Method: A total of 105 maternal death cases were analyzed. The majority of the cases were married, had low education levels, and were covered by the Social Security Institution or the “Green Card” system. Syrian refugees accounted for 9.5% of maternal deaths, with partial differences observed in their access to healthcare services.Result: The majority of maternal deaths resulted from direct (34.3%) and indirect (50.5%) causes. It was determined that the number of consultations with an obstetrician was higher in direct maternal deaths and lower in coincidental deaths. The cesarean section rate was high (72.4%), and deaths predominantly occurred during the postpartum period (72.4%). Most deaths took place in tertiary healthcare institutions, with an increase in mortality rates observed during shift hours.Conclusion: To reduce maternal mortality, it is recommended to strengthen primary healthcare services, control cesarean section rates, and develop more inclusive health policies for refugees. This study provides significant data for determining policies to prevent maternal mortality and increasing the effectiveness of healthcare services.
Keywords: Maternal death; Mortality; Refugee; Health Care; Pregnancy; Public Health